2019
DOI: 10.1021/acs.jmedchem.9b00908
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Strategy of Novel Peptide-Based Michael Acceptors for the Treatment of Human African Trypanosomiasis

Abstract: This paper describes an optimization strategy of the highly active vinyl ketone 3 which was recognized as a strong inhibitor of rhodesain of Trypanosoma brucei rhodesiense, endowed with a k second value of 67 × 106 M–1 min–1 coupled with a high binding affinity (K i = 38 pM). We now report a new structure–activity relationship study based on structural variations on the P3, P2, and P1′ sites which led us to identify two potent lead compounds, i.e., vinyl ketones 4h and 4k. Vinyl ketone 4h showed an impressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 53 publications
(102 reference statements)
1
49
0
Order By: Relevance
“…Several authors have demonstrated that the inhibition of rhodesain is dependent on the peptidic framework of the inhibitor [5,6,10,28–35] . Diederich and co‐workers, [28] in a structure‐based study of nitrile‐derived rhodesain inhibitors, showed that variations in the S1 pocket had weak effects on selectivity of this enzyme; moreover, rhodesain preferred extended hydrophobic for its S2 pocket, while the S3 pocket shows clear preference for aromatic substituents.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have demonstrated that the inhibition of rhodesain is dependent on the peptidic framework of the inhibitor [5,6,10,28–35] . Diederich and co‐workers, [28] in a structure‐based study of nitrile‐derived rhodesain inhibitors, showed that variations in the S1 pocket had weak effects on selectivity of this enzyme; moreover, rhodesain preferred extended hydrophobic for its S2 pocket, while the S3 pocket shows clear preference for aromatic substituents.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, as the newly devised ligands covalently bind to the enzyme, it was necessary to employ a specific docking protocol devised by Bianco et al., namely the “flexible side chain method”. The latter was also succesfully applied in our previous works on convalent Rhodesain inhibitors . This computational method requires the modification of the residue which takes part in the covalent bond and to attach it to the ligand; during the docking calculation, this modified residue is treated as flexible.…”
Section: Methodsmentioning
confidence: 99%
“…In this medicinal chemistry area, our research team has been involved in the last decade into the development of potent rhodesain inhibitors . In this paper, starting from the structure of the reversible rhodesain inhibitors 1 a – c , endowed with K i values in the low‐micromolar range (Scheme ), we designed a new series of peptidomimetics 2 a – g able to inactivate the target enzyme, considering that an irreversible inhibition is strongly desirable in the case of a parasitic target.…”
Section: Introductionmentioning
confidence: 99%
“…Roberta Ettari at the University of Messina, Italy, and co-workers synthesized a new series of peptidyl vinyl ketones employing a cross-metathesis reaction as key step. The compounds were kinetically characterized to be potent inactivators of rhodesain [40].…”
Section: Highlighted By Michael Gütschowmentioning
confidence: 99%
“…Italy, and co-workers synthesized a new series of peptidyl vinyl ketones employing a crossmetathesis reaction as key step. The compounds were kinetically characterized to be potent inactivators of rhodesain [40]. One of the lead compounds ( Figure 6) showed an impressive binding affinity for rhodesain (Ki = 0.6 pM), a strong inhibitory effectiveness (k2nd = kinac/Ki = 1,785,000 M −1 s −1 ), sufficient selectivity towards human cathepsin L, the closest human homolog, as well as good antiparasitic activity as determined using an ATP-monitoring system based on firefly luciferase (EC50 = 0.67 μM).…”
Section: Highlighted By Michael Gütschowmentioning
confidence: 99%